THE IMPORTANCE OF AQUATIC THERAPY IN THE TREATMENT OF THE CEREBRAL PALSY IN PRESCHOOL AGE CHILDREN - Haidamac Ana (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
Cerebral palsy (CP) it is known as a condition that occurs in infants or in fetal development of encephalon. The main purpose in this study was to highlight the importance of aquatic therapy used as an alternative method or in parallel with neurological recovery programs at the gym. This alternative method of aquatic therapy has major benefits and may become a priority of all exercises, in very many cases, after a complex evaluation of children diagnosed with CP. The study was done on a group of six children diagnosed with CP and no surgery till the beginning of aquatic therapy, aged between 3 and 7 years, the period from October 2016 and until May 2018. It was observed an important improvement of the quality life and daily activities and the visible increase of the general symptoms of the children diagnosed with infantile CP. The aquatic therapy used methods of neuro-motor recovery treatments, individually and in groups and various interactive exercises of breathing, spinning of the body in water, flips underwater, all these improving balance, gait, stability, improve the awareness and abilities of the body, facilitating breathing, decrease of spasticity, and last but not least, the joy of immersion in the warm water have immediate effects in relaxation.